Annoyance of residents induced by wind turbine obstruction lights: A cross-country comparison of impact factors. (September 2021) - Pohl, Johannes; Rudolph, David; Lyhne, Ivar; Clausen, Niels-Erik; Aaen, Sara Bjørn; Hübner, Gundula; Kørnøv, Lone; Kirkegaard, Julia K.
Abstract: Larger wind turbines are developed to harvest greater amounts of wind energy. This development increases the dilemma between ensuring aviation safety through obstruction lights and reducing citizen annoyance and possible stress effects caused by obstruction lights. In this study, a unique Danish sample is contrasted with a combined German-Swiss sample. Stronger stress effects due to the lights for the Danish sample compared to the German-Swiss study were found, an issue that could be related to the specific technical and site conditions. The prevalence of strongly annoyed residents was low. Significant factors for predicting obstruction light annoyance stress were identified, including: perceived fairness, consideration of the interests of the community, landscape change annoyance stress, number of visible wind turbines and age. It is recommended to enhance the planning process to reduce the stress among citizens, e.g. through improved communication, and to enhance the participation of residents in a way that allows for a meaningful consideration of people's concerns. Highlights: Stress effects from obstruction lights at wind turbines are assessed. Obstruction lights can induce strong stress effects under certain conditions. Perceived fairness and stress during planning process are significant predictors. Distance to wind turbines is not correlated with obstruction light annoyance stress.